Secure by Design: Cybersecurity Extensions to Project Management Maturity Models for Critical Infrastructure Projects - Jay Payette; Esther Anegbe; Erika Caceres; Steven Muegge (Technology Innovation Management Review, 2015)
Many systems that comprise our critical infrastructures – including electricity, transportation, healthcare, and financial systems – are designed and deployed as information technology (IT) projects using project management practices. IT projects provide a one-time opportunity to securely "design in" cybersecurity to the IT components of critical infrastructures. The project management maturity models used by organizations today to assess the quality and rigour of IT project management practices do not explicitly consider cybersecurity. This article makes three contributions to address this gap. First, it develops the argument that cybersecurity can and should be a concern of IT project managers and assessed in the same way as other project management capabilities. Second, it examines three widely used cybersecurity maturity models – i) the National Institute of Science and Technology (NIST) framework for improving critical infrastructure cybersecurity, ii) the United States Department of Energy’s Cybersecurity Capability Maturity Model (C2M2), and iii) the CERT Resilience Management Model (CERT RMM) from the Carnegie Mellon Software Engineering Institute – to identify six cybersecurity themes that are salient to IT project management. Third, it proposes a set of cybersecurity extensions to PjM3, a widely-deployed project management maturity model. The extensions take the form of a five-level cybersecurity capability perspective that augments the seven standard perspectives of the PjM3 by explicitly assessing project management capabilities that impact the six themes where IT project management and cybersecurity intersect. This article will be relevant to IT project managers, the top management teams of organizations that design and deploy IT systems for critical infrastructures, and managers at organizations that provide and maintain critical infrastructures.
Keywords: C2M2; capability maturity models; CERT RMM; critical infrastructures; cybersecurity; NIST; P3M3; PjM3; project management

Resolving Legitimacy Deficits in Technology Startups through Professional Services Practices - Jay Payette (Technology Innovation Management Review, 2014)
As new ventures, technology startups face a key challenge that is specifically associated with their young age: a perceived lack of organizational legitimacy. Organizational legitimacy is an important factor in the growth and survival of new ventures and is therefore an important issue for managers and entrepreneurs to address. Although there are many different typologies for defining types of organizational legitimacy, this article argues that technology startups should focus on developing external pragmatic legitimacy as a means of acquiring the resources required to grow and thrive. However, despite the many ways by which an organization can develop external pragmatic legitimacy, few are well suited to technology startups. Based on a review of the different types of organizational legitimacy and an assessment of their applicability to the context of technology startups, this article recommends that technology entrepreneurs should consider the creation of professional services practices to help develop external pragmatic legitimacy and overcome the “liability of newness”.
Keywords: entrepreneurship; impression of viability; legitimacy; new ventures; operational verification; organizational legitimacy; pragmatic legitimacy; pragmatic validation; professional services; technology startups; viability